Les magasins-entrepôts de Montréal, 1850 à 1880 : formes et fonctions commerciales. Un nouveau regard - Burgess, Joanne; Lauzon, Gilles (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Magasins

Dupuis Frères: le magasin du peuple: plus d'un siècle de fierté québécoise - Dupuis-Leman, Josette (Stanké, 2001)
Keywords: Commerce de détail; Dupuis Frères; Magasins

Le magasin Dupuis Frères de Montréal: les transformations dans le temps et l'espace d'une institution urbaine, 1868-1978 - Turgeon, Alain (Université de Sherbrooke, 2005)
Keywords: Commerce de détail; Dupuis Frères; Magasins

Étalages, vitrines, services et nouveaux espaces. Trois grands magasins de Montréal durant les années 1920 - Comeau, Michelle (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Commerce de détail; Dupuis Frères; Eaton; Magasins; Morgan

Omer DeSerres. Trois générations créatives - DeSerres, Hélène (Éditions de l'Homme, 2008)
Keywords: Magasins

La maison J. A. Gagnon - Hachey, Jean-Marie (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
issued: 2006-24-00
Keywords: Magasins

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

"Behind the Store": Montreal Shopkeeping Families between the Wars - Taschereau, Sylvie (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Alimentation; Famille; Magasins

Origin and Evolution of the Department Store - Tamilia, Robert D. (Université du Québec à Montréal et Centre de recherche en gestion, 2002)
Keywords: Commerce de détail; Magasins

The Mail Order Catalogue : An Achievement in Mass Distribution and Labour - Willis, John (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Commerce de détail; Magasins

Le voyage virtuel. Les consommatrices, le monde de l'étranger et Eaton à Montréal, 1880-1980 - O'Donnell, Lorraine (Revue d'histoire de l'Amérique française, 2005)
issued: 2005-21-00
Keywords: Eaton; Femmes; Magasins

Le repositionnement du centre-ville de Montréal dans la structure commerciale régionale; un examen des comportements d'achat de ses travailleurs de bureau - Mercier, Charles-Olivier (Université de Montréal, 2006)
Keywords: Centre-ville; Magasins; Quartiers

Figures du libraire au Québec - Brisson, Frédéric (Documentation et bibliothèques, 2005)
issued: 2005-04/2005-06
Keywords: Beauchemin (librairie); Librairie; Magasins

Entrepreneuriat et travail dans un commerce engagé: exploration du sens et panorama des pratiques des acteurs - Jauzion, Catherine (Université du Québec à Montréal, 2008)
Keywords: Cafés; Magasins; Restaurant; Travail

Christmastime chez Dupuis Frères - Dupuis-Leman, Josette (The Beaver, 2005)
issued: 2005-12/2006-01
Keywords: Commerce de détail; Dupuis Frères; Magasins

Commerces du coin - Giroux, Éric (Écomusée du fier monde et arrondissement Ville-Marie, 2009)
Keywords: Commerce de détail; Magasins; Quartiers; Sainte-Marie

Institutions commerciales de Verdun. D'hier à aujourd'hui (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
issued: 2006-24-00
Keywords: Commerce de détail; Confection; Magasins; Quartiers; Quincaillerie; Verdun; Vêtements; Épicerie